2010
DOI: 10.1021/ac902858b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecule Size on Its Transport Properties through a Porous Medium

Abstract: The mass transfer kinetics of toluene and polystyrenes (of which the M(w) varies from 162 to 1.85 x 10(6) g mol(-1)) through columns filled with silica porous spheres were studied by inverse size exclusion chromatography. The mass transfer parameters were measured by modeling the band broadening of the chromatograms. The experimental height equivalent to a theoretical plate (HETP) data were analyzed using the general rate model in order to determine the effective diffusion coefficient in porous particles as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…As such, we used this constant offset between each set of plots, in combination with Eq. (9), to obtain the D m in THF of PMMA with M < 30,000 g/mol (applying a similar procedure to PS < 30,000 g/mol yielded D m that very closely matched those measured by Wernert et al in reference [27]). …”
Section: Results From Our Experiments Are Shown Insupporting
confidence: 62%
See 1 more Smart Citation
“…As such, we used this constant offset between each set of plots, in combination with Eq. (9), to obtain the D m in THF of PMMA with M < 30,000 g/mol (applying a similar procedure to PS < 30,000 g/mol yielded D m that very closely matched those measured by Wernert et al in reference [27]). …”
Section: Results From Our Experiments Are Shown Insupporting
confidence: 62%
“…For PS in THF, D m were Table 1 Intraparticle obstruction factor ( p ) values for PS and PMMA at both 30 and 50 • C for a 8 m particle size, 10 4Å pore size column. obtained from [27]:…”
Section: Results From Our Experiments Are Shown Inmentioning
confidence: 99%
“…To the best of our knowledge, Inverse Liquid Chromatography (ILC) to study mesoporous alumina supports has never been reported in the literature so far. Nevertheless, the use of ILC to characterize transport properties of large molecule in silica has already been reported [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The tortuosity factor as function of accessible pore volume fraction is plotted in Figure 14, compared with an experimental reference by Inverse Size Exclusion Chromatography (ISEC) with p = 2.4 [5] plotted in blue dotted curve.…”
Section: Tablementioning
confidence: 99%
“…Its applicability has been experimentally assessed by permeability [9], electrical conductivity [11] or effective diffusion [5] measurements. Hindered diffusion coefficient in nanoporous solids can be measured by proton Pulsed-Field Gradient Nuclear Magnetic Resonance (PFG-NMR) [12], inverse chromatography [5], membrane permeation or modeling of the kinetics of adsorption of the solute in a batch reactor [13,14]. It is worth mentioning that PFG-NMR measures a self-diffusion coefficient, and the measurement is done only in the part of the pore space that is accessible by the probe molecule.…”
Section: Introductionmentioning
confidence: 99%